Total productive maintenance and companies performance: a case study of fast moving consumer goods companies - Oroye, Olufemi Adebayo; Sylvester, Bamisaye Olufemi; Farayibi, Peter Kayode (Jurnal Sistem dan Manajemen Industri, 2022)
TPM implementation by FMCG firms in Ado/Ota industrial hub of Ogun State Nigeria was investigated, and its influence on the firm's performance was analyzed. Primary data were collected through the administration of an online questionnaire. A total number of 98 respondents participated in this research. The analysis was conducted through descriptive analysis and structural equation model (SEM) using a smart partial least square (PLS) software. It was observed that TPM implementation had a positive influence on firms' performance. The descriptive analysis. It noted that most firms explored in this study had implemented TPM. It implies that above ninety percent of companies in the industrial hub are practicing TPM. The data employed in this research are limited to those obtained from FMCG firms in Ado/Ota in Ogun State, Nigeria. However, this study's findings can represent other firms in other locations where TPM is practiced. This research will be helpful for FMCG firms in Nigeria, especially those in Ogun State. TPM was measured using the following indicators: 5S, Autonomous Maintenance, Kobetsu Kaizen, Planned Maintenance, Quality, Education and Training, Office TPM, and Health, Safety and Environment. Eight indicators measure The company's performance: Product Quality, Cost, Inventory, Lead Time, Processing Cycle Time, Customer Complaints, Equipment Efficiency and Overall Productivity. The research review shows that the TPM implementation significantly affects firms' sustainable performance. In addition, the result shows that local firms in the survey area are yet to key into implementing TPM practices fully.